Financial ratios communication - Aripin, Norhani; Tower, Greg; Taylor, Grantley (2010)
This study examines the relationship between ownership concentration and the extent of financial ratio disclosures (EFRD) in the 2007 annual reports of Australian listed firms. Using agency theory as theoretical background, it is suggested that firms with more concentrated ownership structures are less likely to provide voluntary disclosure of financial ratios information. The univariate tests demonstrate that profitable firms, those firms audited by Big4 auditors and firms belonging to financial services industry communicate more financia1 ratio information.OLS regressions show that more dispersed shareholding firms' are significantly associated with EFRD. Profitable and larger firms audited by independent and Big4 audit firms additionally reported more extensive financial ratio information.